2011
DOI: 10.1007/s11060-011-0739-6
|View full text |Cite
|
Sign up to set email alerts
|

Primary central nervous system post-transplant lymphoproliferative disorders following allogeneic hematopoietic stem cell transplantation

Abstract: Post-transplant lymphoproliferative disorder (PTLD) is a serious complication after allogeneic hematopoietic stem cell transplantation (HSCT). Extra nodal involvement is common in PTLD, but isolated involvement of the central nervous system (CNS) is extremely rare. Given the rarity of primary CNS-PTLD there is no consensus on optimal treatment. We report a patient who developed Epstein-Barr virus related primary CNS-PTLD following allogeneic HSCT who was treated with the monoclonal anti-CD20 antibody rituximab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 36 publications
(33 reference statements)
1
31
0
1
Order By: Relevance
“…38 In solid organ transplant recipients the median time to CNS-PTLD is 4.4 years, 38 while in CNS-PTLD patients who received allo-HSCT disease developed after 2e24 months. 40,41 In both types of transplant, M:F ratio is about 2. 38 The primary CNS-PTLD needs to be considered separately as it has significantly inferior survival compared to non-CNS PTLD and its therapy is different than in other forms of PTLD.…”
Section: Monomorphic Ptldmentioning
confidence: 98%
“…38 In solid organ transplant recipients the median time to CNS-PTLD is 4.4 years, 38 while in CNS-PTLD patients who received allo-HSCT disease developed after 2e24 months. 40,41 In both types of transplant, M:F ratio is about 2. 38 The primary CNS-PTLD needs to be considered separately as it has significantly inferior survival compared to non-CNS PTLD and its therapy is different than in other forms of PTLD.…”
Section: Monomorphic Ptldmentioning
confidence: 98%
“…4 This disorder encompasses a heterogeneous group of disorders that can range from an indolent polyclonal proliferation to aggressive lymphomas. 5 Posttransplant lymphoproliferative disorder is thought to be the result of immunosuppressive-induced impairment of T-cell immunity, leading to an uncontrolled proliferation of EBVtransformed B lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…4,10,13 Prospective and retrospective studies using rituximab with temozolomide in primary CNS lymphoma have shown it to be an effective and well-tolerated treatment modality. 3,14 Evens and associates showed by univariate analysis that treatment with rituximab was associated with a significant improvement in PFS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Till date, only 14 cases have been reported in the literature, and none occurred in lymphoma patients. [2,3] In this paper, we report the first case of a B-cell lymphoma presenting with an isolated PTLD in the CNS after HSCT.…”
Section: Introductionmentioning
confidence: 97%